2018
DOI: 10.1016/j.vph.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a novel truncating mutation in Lamin A/C gene in a family with a severe cardiomyopathy with conduction defects

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND) (http://www.karger.com/Services/OpenAccessLicense). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For instance, alterations in several cellular pathways, including WNT/β‐catenin, mitogen‐activated protein kinases (MAPKs) and protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signalling, have been identified in LMNA H222P/H222P mice, a mouse model of the human LMNA‐associated DCM‐CD 5,6 . Interestingly, lmna mutations may also impinge the machinery involved in Ca 2+ handling into the ER 7–9 and the connexin 43 (CX43) expression/activity at the plasma membrane in cardiomyopathies 10,11 . More recently, Salvarini et al demonstrated that the epigenetic inhibition of the sodium voltage‐gated channel alpha subunit 5 (SCN5A) in cardiomyocytes differentiated from IPS derived from patients with K219T‐LMNA pathogenic variant 12 can account for the conduction defects reported in the clinical history of these arrhythmogenic patients.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, alterations in several cellular pathways, including WNT/β‐catenin, mitogen‐activated protein kinases (MAPKs) and protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signalling, have been identified in LMNA H222P/H222P mice, a mouse model of the human LMNA‐associated DCM‐CD 5,6 . Interestingly, lmna mutations may also impinge the machinery involved in Ca 2+ handling into the ER 7–9 and the connexin 43 (CX43) expression/activity at the plasma membrane in cardiomyopathies 10,11 . More recently, Salvarini et al demonstrated that the epigenetic inhibition of the sodium voltage‐gated channel alpha subunit 5 (SCN5A) in cardiomyocytes differentiated from IPS derived from patients with K219T‐LMNA pathogenic variant 12 can account for the conduction defects reported in the clinical history of these arrhythmogenic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we demonstrated that such variant mis-localized and accumulated into the ER when expressed in mature cardiomyocytes, as expected from the absence of the nuclear localization sequence (NLS), inducing ER dysfunction and the up-regulation of pro-apoptotic markers (Figure 1 and 2). Of note, a very similar truncated variant of LMNA misplaced into the ER when expressed in cardiomyocytes but induced a severe cardiomyopathy by a different pathogenic mechanism (18). These findings clearly indicate that each Lmna mutation drives cardiac detriment by its own and unique pathway and that ER stress induced by the accumulation of LMNA R321X into ER might be a useful pharmacological target in the LMNA R321X associated cardiac laminopathy.…”
Section: Discussionmentioning
confidence: 84%
“…This finding suggests that the pathogenetic mechanism of the cardiomyopathy in the nonsense mutation group might be related to either the dominant negative effect or cytotoxic effect of the resulting truncated LMNA protein rather than exclusively haploinsufficiency of LMNA wild type. Accordingly, we and others demonstrated that truncated pathogenic variants of LMNA were expressed into the heart of the carriers and may induce abnormal degradation of the WT LMNA (16) or interfere with cardiomyocytes homeostasis (17); (18); (13). Specifically, we previously characterized nonsense Lmna mutation that introduces a premature termination codon within the 6th of 12 Lmna exons corresponding to a truncated variant in the central a-helical coiled-coil rod domain (coil 2B) of the LMNA protein, R321X.…”
Section: Introductionmentioning
confidence: 99%